Purification of used sunflower frying oil with adsorbent mixtures using an active filtration method - Turan, S.; Yalcuk, A.; Sislioglu, K.; Ramadan, M. F. (Innovhub Ssi-Area Ssog, 2019)
In this study, purification of used frying sunflower oil was investigated using different adsorbents and their mixtures. The effective adsorbents in reducing the free fatty acid (FFA) content, total polar material (TPM) and the p-Anisidine value (AV) as well as in lightening of the colour, when used in single-use, were aluminium oxide (AO), silica gel (SG), activated charcoal (AC) and bleaching earth (BE). Increasing the adsorbent ratio from 3% to 6% improved the quality of the used oil. Among the binary adsorbent mixtures, 6%AO+6%AC reduced FFA content by 79.1% and the AV by 56.8%. The ternary adsorbent mixtures reduced the conjugated diene (CD) content of oil in the following order 3%SG+3%M+3%B, 3%AO+3%AC+6%Z, 3%AO+3%M+3%B and 3%AO+3%M+3%Z, respectively, providing a percentage improvement (PI) in the range of 60-100%. The binary adsorbent mixture reduced the viscosity of the used oil. The highest value was 3%AO+6%SG (42.6%), whereas the following ternary mixtures of 3%AO+3%SG+3%AC (48.4%) and 3%AO+3%SG+3%B (47.6%) were the most successful. The utilisation of adsorbents singly or in either binary or ternary mixtures resulted in increasing the L* value of the used oil and decreasing the a* and b* values. The adsorbents and their mixtures are believed to be useful in the purification of used oil.
Keywords: Active filtration; bleaching earth; used frying oil; adsorbent mixtures; free fatty acid